Anti-proliferative activity and structure-activity relationship of honokiol derivatives. Issue 16 (15th August 2019) - Lin, Ding; Yan, Zhongzhong; Chen, Aiyu; Ye, Jiao; Hu, Aixi; Liu, Juan; Peng, Junmei; Wu, Xiaoyun
Graphical abstract: Abstract: As a known natural product with anti-tumor activity, honokiol has been widely researched and structural modified. Lots of honokiol derivatives have been found to possess good anti-proliferative activity and showed great potential in cancer therapy, but the SAR (structure-activity relationship) was still confused. Here in, the SAR were comprehensively researched by summary of reported derivatives and synthesis of novel derivatives. Amongst novel derivatives, the promising compoundsA6 andA10 exhibited potent and selective anti-proliferative activities against K562 cell line with the IC50 values of 5.04 and 7.08 μM respectively. The SAR was discussed around honokiol and 79 derivatives by the means of CoMFA and theoretical calculation, which provided useful suggestion for further structural optimization of honokiol derivatives.